Shelf life de duas variedades de mangaba endêmicas do Cerrado - Coelho, Beatriz Leão de Lacerda; Nascente, Letícia de Paula; Braz, Aline Jordane; Corrêa, Nayara Canêdo; Araújo, Isabela Rosa de; Perfeito, Danielle Godinho Araújo; Souza, Eli Regina Barboza de; Siqueira, Ana Paula Silva (Multi-Science Journal, 2017)
Não há.